Spontaneous emission of a quantum emitter near a Chern insulator : interplay of time-reversal symmetry breaking and Van Hove singularity - Lu, Bing-Sui (2021)
We consider the generic problem of a two-level quantum emitter near a two-dimensional Chern insulator in the dipole approximation, and study how the frequency-dependent response and electronic density of states of the insulator modifies the transition rate of the emitter between the ground and excited levels. To this end, we obtain the full real-frequency behavior of the conductivity tensor by performing a tight-binding calculation based on the Qi-Wu-Zhang model and using a Kubo formula, and derive the full electromagnetic Green tensor of the system, which breaks Onsager reciprocity. This enables us to find that for frequencies smaller than the maximum band gap, the system is sensitive to time-reversal symmetry breaking, whereas for much larger frequencies the system becomes insensitive, with implications for the discrimination of the state of a circularly polarized dipole emitter. We also study the impact of a Van Hove singularity on the surface-induced correction to the transition rate, finding that it can enhance its amplitude by a few orders of magnitude compared to the case where the conductivity is set to its static value. By considering configurations in which the dipole is circularly polarized or parallel with the surface of the Chern insulator, we find that the surface correction to the transition rate can exhibit a novel decay with sine-integral-like oscillations.